2004
DOI: 10.1188/04.onf.1069-1075
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, Weight Gain, and Altered Sexuality in Patients With Breast Cancer: Exploration of a Symptom Cluster

Abstract: Nurses should view symptoms caused by breast cancer treatment holistically, keeping in mind that a reciprocal relationship often exists among symptoms. Identification of symptom clusters with empirically derived interventions may enhance quality of care and quality of life for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
0
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 59 publications
0
45
0
9
Order By: Relevance
“…3,4 Despite an awareness that toxicities rarely occur independent of each other, the majority of research in supportive cancer care has focused only on individual symptoms, such as fatigue, 5 mucositis, 6 anxiety or alopecia, 7 nausea/vomiting, hematologic toxicity, 9 or pain. 10 This paradigm is currently shifting to the study of symptom clusters, [11][12][13] most of which have been defined using conventional hierarchical analysis.…”
mentioning
confidence: 99%
“…3,4 Despite an awareness that toxicities rarely occur independent of each other, the majority of research in supportive cancer care has focused only on individual symptoms, such as fatigue, 5 mucositis, 6 anxiety or alopecia, 7 nausea/vomiting, hematologic toxicity, 9 or pain. 10 This paradigm is currently shifting to the study of symptom clusters, [11][12][13] most of which have been defined using conventional hierarchical analysis.…”
mentioning
confidence: 99%
“…Entre los factores etiológicos pueden nombrarse la fatiga experimentada, la menopausia temprana, la sensación de sofoco, el dolor en la relación sexual (dispareunia), cambios en el estado de ánimo, así como la resequedad vaginal que pueden disminuir las respuestas sexuales consideradas normales y alterar la percepción de intimidad en la mujer (17,18) . En un estudio de Schag et al (1993), donde se evaluaron las características de mujeres en riesgo de sufrir de malestar psicológico un año después del diagnóstico de cáncer de mama, se encontró que más de un tercio de estas mujeres se quejan de alteraciones en su vida sexual (19) .…”
Section: Evidencia Que Sugiere Dificultades En La Sexualidadunclassified
“…Por último pero no menos importante está el tratamiento de radioterapia, responsable por cambios en la piel provocados por la radiación (e.g., eritemas y quemaduras). Estos efectos no suelen ser prolongados en el tiempo, y generalmente han desaparecido algunos meses después del procedimiento por lo que la mujer no experimenta un impacto sustancial en su calidad de vida (18,49) . Desafortunadamente, en los casos más graves existe la posibilidad de que se registren manifestaciones cróni-cas derivadas de la radiación en el seno, que incluyen la pigmentación de la piel, retracción, eritema, fibrosis y que resulta en una reducción de la estética del seno y de la movilidad del brazo (42,52,53) .…”
Section: Evidencia Que Sugiere Dificultades En La Sexualidadunclassified
“…Furthermore, if these symptom clusters arise from a common mechanism and are amenable to a common intervention, clinicians can then manage and treat multiple symptoms within the same cluster, which may lead to improvements in quality of life, adherence to treatment, and therapeutic benefit. [9][10][11] In recent years, symptom clusters have been evaluated across a variety of cancers, [12][13][14] with several studies in breast cancer, [15][16][17] lung cancer, [18][19][20] and non-Hodgkin lymphoma 21 and across multiple cancer sites. [22][23][24][25][26][27][28][29][30][31][32] Each of these studies prospectively collected patient-reported symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies used the MD Anderson symptom inventory, 11,29 whereas others used self-developed symptom checklists. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]28 The level of detail with which symptoms are collected and the symptoms that are included vary across these instruments. The lack of uniformity regarding selected symptoms scales and instruments likely contributed to the lack of consistency of the symptom clusters identified.…”
Section: Introductionmentioning
confidence: 99%